Concise Review: Recent Advances in Molecular Dynamics Simulation of Nanomachining of Metals - Zhang, Junjie; Wang, Zhanfeng; Yan, Yongda; Sun, Tao (Current Nanoscience, 2016)
Background: Nanomachining techniques not only provide novel opportunities to fabricate three-dimensional nanostructures, but also induce great challenges in understanding their machining mechanisms at the nanometer scale. While nanomachining exhibits a strong dependence on chemical, physical and mechanical properties of workpiece materials, the molecular dynamics (MD) simulation has been demonstrated to be a powerful tool to explore the materialoriented nanomachining process. In this concise review we focus on the recent scientific progress in MD simulation of nanomachining of metals with different microstructures. Methods: The construction of atomic structures of single crystalline, bicrystal and nanocrystalline metals is first presented. Then MD models of nanomachining with different modes, i.e., load-controlled and displacement-controlled, are discussed. Since defect evolution plays an important role in plastic deformation of metals, finally advanced techniques of lattice defects for identifying types of dislocation and grain boundary (GB) are reviewed. Results: According to different microstructures of workpiece materials, MD simulations of nanomachining of metals are categorized into three parts, i.e., single crystalline, bicrystal and nanocrystalline. For single crystalline metals that plastic deformation is dominated by dislocation mechanisms, aspects of workpiece properties dependence, tool geometry dependence, tool/chip interface, thermal effect, machining direction, tool wear and mechanical properties of machined surface are reviewed. For bicrystals that containing GBs, dislocation-GB interactions and their correlation with machining results are emphasized. For more complex nanocrystalline metals with crystallites of varying size and orientation, the GB accommodation and deformation twinning found in nanomachining of metals are discussed, in addition to dislocation mechanisms and dislocation-GB interactions. Furthermore, grain size dependence of nanomachining is also addressed. Finally, current limitations and future prospections on MD simulations of nanomachining are also addressed in terms of empirical potential, length and time scale, tool wear and chemistry. Conclusion: This concise review of MD simulation of nanomachining demonstrates the strong dependence of nanomachining on the microstructure and properties of workpiece materials, which not only provides theoretical fundamentals for nanomachining experiments, but also is important for the rational synthesis or preparation of nanostructured materials with good machinability at the nanometer scale.
Keywords: nanomachining